The nutritional value of food service meals ordered by hospitalized children. (October 2016) - Huang, Jeannie S.; Chun, Stanford; Cheung, Christopher; Poon, Linda; Terrones, Laura
Summary: Background and aims: US hospitals routinely provide food to hospitalized children. The nutritional content of provided foods has not been evaluated. We performed our study to examine meal orders of hospitalized youth and determine whether the nutritional contents of ordered meals meet dietary guidelines. Methods: We performed a cross-sectional evaluation among hospitalized youth ≥1 y receiving all nutritional intake by mouth and not on a clear liquid diet. Meal orders from hospitalized youth were analyzed for nutritional content. Daily calories, fiber, protein, fat content, and sugar-sweetened beverages ordered were determined and compared with published dietary recommendations. Distribution analyses and odds ratios for meeting v. not meeting dietary recommendations were calculated for select factors and adjusted for hospital length of stay. Results: 969 meal orders from 247 patients [13 (1, 26) [median (min, max)] years, 50% male, 47% Hispanic] at a tertiary care pediatric hospital were reviewed. Forty-four percent of daily meals exceeded caloric recommendations, 9% met fiber recommendations, 36% met fat recommendations, all met protein requirements, and 53% included sugar-sweetened beverages. Overweight/obese boys <13 y hospitalized ≤7 d were more likely to place meal orders exceeding daily caloric recommendations while Hispanic overweight/obese youth hospitalized ≤7 d were more likely to order sugar-sweetened beverages than inpatient counterparts. Conclusions: Pediatric hospital meal orders commonly do not meet dietary guidelines. Hospitals should encourage youth and families to order within nutritional guidelines to prevent additional health risk.